Evaluation of grain yield and quality in maize hybrids of various origin under the conditions of Primorsky Territory - E. S. Butovets; I. N. Danilenko; N. A. Kraskovskaya (Труды по прикладной ботанике, генетике и селекции)
Background. This study was dedicated to the evaluation and selection of maize hybrids of different origin for important agronomic traits and for protein and oil accumulation in grain under the conditions of Primorsky Territory, as well as for their possible use as source material for breeding.Materials and methods. Twenty-two grain maize hybrids of various geographic origin were studied at the Federal Scientific Center of Agricultural Biotechnology of the Far East named after A.K. Chaika” in 2017–2020. Useful agronomic characters and biochemical indications were assessed, correlations between parameters were established, and an integrated evaluation of maize hybrids was made. The hybrids were ranked relative to a predetermined ideal model.Results. Based on the results of the integrated assessment, maize hybrids Р 7709, Р 8688 and Р 8523 (Pioneer Corporation) and Si Rotango (Syngenta) had the highest scores for a set of important agronomic traits under the conditions of Primorsky Territory. Higher protein content levels were detected in maize grain when the combination of temperature and moisture was optimal (Selyaninov’s hydrothermal coefficient = 1.1). The highest oil content was observed at an enhanced level of soil moisture (HTC = 3.1). The Si Rotango hybrid had the maximum protein content. The NUR, Ladozhsky 181 MV and P 7054 hybrids showed the maximum in oil content. Strong direct correlations were discovered between the yield and the weight of 1000 kernels and one ear, and between grain yield and the height of the lower ear position. Weak reverse correlations were observed between biochemical parameters and yield, and between a FAO maturity group and grain yield.